Anne Boleyn in Popular Fiction - Runštuková, Iveta (Univerzita Pardubice, 2014)
The subject of this master thesis is Anne Boleyn, Queen of England living in the sixteenth century, and the second wife of King Henry VIII. This thesis deals with the portrayal of Anne Boleyn in the two popular fiction novels, The Lady in the Tower by Jean Plaidy and The Other Boleyn Girl by Philippa Gregory. Firstly, popular fiction is characterised, especially the genre of popular biography which is compared to the genre of authentic biography. Then the attention is focused on the selected aspects of Anne Boleyn's life, such as family background, education, character and beliefs, possible reasons of her fall into disgrace, and her death. This paper presents, analyzes and compares the possibilities of the image of the historical personage in popular literature with the help of so far available historical information.
Anna Boleynová v populární fikci
Keywords: Anne Boleyn; Tudors; sixteenth century; popular fiction; Jean Plaidy; Philippa Gregory; Anna Boleynová; Tudorovci; šestnácté století; populární fikce